DETERMINAN KEPUTUSAN PEMBELIAN PRODUK PADA KING BOBA CAFÉ DITINJAU DARI ASPEK PEMILIHAN LOKASI DAN DESAIN INTERIOR - Sutanty, Marisa; Afriani, Enggal Ardiastul (Fakultas Ekonomi dan Manajemen, 2024)
This study aims to know the determinants of product purchase decisions at King Boba Cafe reviewed from the aspect of location selection and interior design. The type of this study was associative research which aims to examine the effect of location (X1) and interior design (X2) as independent variables, on product purchasing decisions at King Boba Café (Y) as dependent variables. The type of data used was quantitative data collected directly by researchers from research respondents using a research instrument in the form of a questionnaire. The sample used in this study was 96 customers at King Boba Café. Respondent selection was carried out using probability sampling techniques with the accidental sampling method. Data analysis tools were performed using multiple linear regression analysis techniques, t test, F test, and the coefficient of determination (R2) test. The results of this study showed that location and interior design had a positive and significant effect on product purchasing decisions at King Boba Café, both partially and simultaneously. The contribution of location and interior design variables in influencing changes on product purchasing decision variables at King Boba Café was 57.4%, while the remaining of 42.6% was effected by other variables outside this research model, such as brand ambassadors, brand experience and brand image.